Behavioral Approaches for Primary Headaches: Recent Advances. Issue 6 (26th May 2018) - Raggi, Alberto; Grignani, Eleonora; Leonardi, Matilde; Andrasik, Frank; Sansone, Emanuela; Grazzi, Licia; D'Amico, Domenico
Abstract : Background: Behavioral treatments in the management of primary headache disorders in adults and children are increasingly being recognized as effective; however, the level and durability of their effectiveness is still a matter of debate. This review aims to provide more updated information on the effects of behavioral therapies in adults and adolescents with primary headache disorders, with a special focus on new and emerging behavioral treatments. Methods: We searched SCOPUS for peer‐reviewed papers that reported randomized controlled trial or observational studies addressing behavioral treatment for headache disorders published in the period January 2010 to October 2017. Results: A total of 22 publications, in which 2110 participants were recruited, were included in the review. Most of the studies referred to cognitive behavioral therapies, and a reduction of headache frequency higher than 35% was generally reported irrespective of the approach. In addition, valuable impact disability and quality of life was observed, as well as improvements in depression, anxiety, self‐efficacy, and intake of medications. Conclusions: Behavioral approaches are effective and less prone to produce side or harmful effects, which makes them a valid option particularly for women who are pregnant or nursing, people with other chronic conditions requiring pharmacological treatments putting them at risk for drug‐drug interactions, and children.